STANDARDIZATION OF ELISA AS A TEST FOR ESTIMATION OF ASVS IN EQUINE SERA - MUGESH SANKARANARAYANAN; MUGESH SANKARANARAYANAN; VASUDEVAN MURALIDHARAN; PRAVEEN KUMAR MUTHU; CHANDRAN MASI; SIVARAMAN SELVARASU; JAYARAMAN PALANIMUTHU; SEKAR BABU HARI RAM (International Journal of Pharma and Bio Sciences, 2011)
Snakebite is a serious medical problem worldwide especially in the tropics and subtropics. Administration of anti-snake venom serum (ASVS) is the only effective treatment for snakebites. Snake venom is used to make antivenom serum from horse as the host. Several methods have been suggested as alternatives to the mouse bioassay for venom toxicity and to determine the potency of polyvalent anti-snake venom serum. The present study is done by using ELISA as an alternative to animal assay in screening the equine sera for the presence of antibodies. In the present study, Cobra venom concentrations ranging from 1ng to 100ng / 100 µl / well were used initially for coating. From this 1ng of Cobra venom was found to be sufficiently enough for estimating ASVS. ASVS dilutions upto 1:128 were used and dilutions exceeding this range were found to have no detectable Antivenom. There was a reduction in the O.D values when the coating time was reduced, but still the O.D values between Neat and negative controls are discriminatory. This protocol if standardized will minimize the time duration of the test.